Peningkatan Hasil Belajar Biologi Melalui Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions - Irawani, Fifi; Lastri, Lastri; Kamsurya, Rizal (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2023)
This study aims to determine the improvement of biology learning outcomes through the application of the Student Teams Achievement Divisions (STAD) type cooperative learning model to grade VIII students of SMP Negeri 4 Salahutu. The type of research used is Classroom Action Research which consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study numbered 34. The instruments used are observation sheets, learning outcome tests, and documentation. Based on the results of data analysis, it was found that the application of the STAD type cooperative learning model can improve student learning outcomes in grade VIII SMP Negeri 4 Salahutu. These results are intended by increasing the results of the initial test, cycle I, and cycle II tests. This is shown from the results obtained by students who have achieved the Minimum Completeness Criteria individually, namely 67 and classically the completeness of student learning reaches 75% of students who are complete. In the initial test, the percentage of student learning completeness only reached 26.47% and increased in the first cycle test to 64.71%, and again increased in the end of the second cycle test to 94.12%. While the average score obtained classically also increased, namely in the initial test the average value obtained was 52.65, there was an increase in cycle I to 69.12 and increased significantly in cycle II to 83.24.